Procedimiento de diagnóstico para la implementación de sistemas de gestión del conocimiento - Ricardo Concepción, Mario A (2021)
Introduction: Knowledge management has established itself as an ideal approach for increasing organizational competitiveness based on the effective use of knowledge. However, the review of the theory that has been generated in this field so far shows the absence of practical tools for the implementation of this form of management from a systemic and integrative perspective. Objective: To propose a diagnostic procedure for the implementation of organizational knowledge management systems. Methods: The procedure was developed through a combination of theoretical and empirical methods of scientific research. It highlights the use of additive linear indicators based on a multi-attribute approach that facilitates the processing of the information obtained at the different stages of the procedure, as well as an analytical matrix that allows the classification of organizations from the perspective of knowledge management. Results: It was obtained a procedure for the diagnosis prior to the implementation of knowledge management systems that consists of four stages and integrates the technological and human resources approaches by means of different facilitating variables. Conclusions: The application of the proposed procedure by organizations that contemplate within their goals the implementation of systems to manage knowledge will allow them to diagnose its state as a basis for the subsequent design of an implementation plan in correspondence with their real strategic situation.